2001
DOI: 10.1557/proc-703-v4.7
|View full text |Cite
|
Sign up to set email alerts
|

Grain-Size-Dependent Thermal Transport Properties in Nanocrystalline Yttria-Stabilized Zirconia

Abstract: Understanding the role of grain boundaries in controlling heat flow is critical to the success of many envisioned applications of nanocrystalline materials. This study focuses on the effect of grain boundaries on thermal transport behavior in nanocrystalline yttriastabilized zirconia (YSZ) coatings prepared by metal-organic chemical vapor deposition. A strong grain-size-dependent reduction in thermal conductivity is observed at all temperatures from 6-480 K. The behavior is due primarily to the effect of inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…(2) has been widely used to study the ETC for many nanocrystalline materials238910111213, in fact, its value calculated by Eq. (2) is usually larger than almost all of the experimental or simulated values3912.…”
mentioning
confidence: 99%
“…(2) has been widely used to study the ETC for many nanocrystalline materials238910111213, in fact, its value calculated by Eq. (2) is usually larger than almost all of the experimental or simulated values3912.…”
mentioning
confidence: 99%
“…In the classical Kapitza formalism, the lattice thermal conductivity is linked to the average grain size as follows:normalλlat.=normalλlat.)(1+RKλnormallat.·1d1…”
Section: Theoretical Modeling Of the Grain Size Dependence Of The Latmentioning
confidence: 99%
“…These models are based on the Debye approximation of phonon density of state and connect R GB to the overlap between the phonon dispersion at the grain‐boundary interface. However, these models fail to predict R GB , in particular at the high‐temperature limit . Nevertheless, in some cases, the acoustic mismatch and diffuse mismatch models can define, respectively, upper and lower limits of R GB .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that with increasing particle velocity and temperature the coating is densified and the thermal conductivity increases 14,15 . The quantitative effect of grain boundaries on the thermal conductivity was analyzed which shows that the thermal conductivity of small grains is lower compared to large grains [16][17][18] .…”
Section: Introductionmentioning
confidence: 99%